The choice of the conditions to receive the electrolytic zinc powders for metal-rich compositions - A. V. Patrushev; T. N. Ostanina; V. M. Rudoy; A. V. Vereshchagina; O. L. Zalesova; A. S. Soloviev; N. I. Shtirba (Chimica Techno Acta, 2015)
In the work a method of obtaining highly dispersed zinc powders by electrolysis and comparison of the properties of zinc-rich compositions prepared using as a pigment zinc powders obtained by different methods is provided. Conducted measurements have shown that the electrical conductivity of zinc-rich coatings comprising electrolytic zinc powder does not inferior to the conductivity of the film with PZHD-0 powder obtained by the  evaporation-condensation method, despite the significant difference in the amount of zinc pigment. On the basis of the received data one can conclude that the use of electrolytic zinc powder as a pigment will significantly save zinc.